Pemanfaatan Biomassa Padat Kelapa Sawit Sebagai Energi Baru Terbarukan DI PLTU Pabrik Kelapa Sawit PT. Perkebunan Nusantara VI Unit Usaha Bunut - Rozlinda Dewi; Umar Djufri; Holfy Wijaya (Universitas Batanghari Jambi, 2022)
Palm oil is one of the choices of growth companies in Indonesia as biomass energy. Biomass is organic matter made from plants and animals that contain energy. The result of the palm oil processing process is liquid and solid waste.Liquid waste in the form of sludge can be reprocessed into pure palm oil with several treatments.Solid waste in the form of shells and fibers (fibre) derived from palm pulp is used as fuel in boilers and used as steam steam for the process of generating electricity through turbines. Research on the utilization of solid palm oil waste fibers and shells was carried out at PT. Nusantara Plantation VI PKS Bunut because of its large waste potential as an alternative fuel source (renewable energy. Processing capacity of the plant of 30 tons of FFB/hour produces 3.9 tons of fiber solid waste and 2.1 tons of shells, the total solid waste as fuel is 6 tons/hour. The fuel requirement of the plant is 4.55 tons/hour so that there is a difference of 1.45 tons/hour. The electrical energy generated from the utilization of 6 tons/hour of fuel is 776 kW/Hour, while the realization energy used by the factory is 750 kWh/Hour.There is an excess energy of 2.6 kW/hour. This indicates that the use of shells and fibers as fuel for new and renewable energy at the PLTU PKS Bunut PT. Nusantara VI plantations are very good.